EuroCrops: The Largest Harmonized Open Crop Dataset Across the European Union - Maja Schneider; Tobias Schelte; Felix Schmitz; Marco Körner (Scientific Data, 2023)
Abstract EuroCrops contains geo-referenced polygons of agricultural croplands from 16 countries of the European Union (EU) as well as information on the respective crop species grown there. These semantic annotations are derived from self-declarations by farmers receiving subsidies under the common agricultural policy (CAP) of the European Commission (EC). Over the last 1.5 years, the individual national crop datasets have been manually collected, the crop classes have been translated into the English language and transferred into the newly developed hierarchical crop and agriculture taxonomy (HCAT). EuroCrops is publicly available under continuous improvement through an active user community.